Developing effective study sheets as a vehicle for learning in museums - Simbarashe Shadreck Chitima (MSU Press, 2023)
The study sheets are a popular medium of content delivery in museums. This study examines how study sheets being employed by national museums in Zimbabwe, promote effective learning of curriculum content among primary school pupils. The study employed the socio-cultural learning framework as the theoretical framework. Qualitative research and phenomenology research design were deployed as research methodology. The study was undertaken from 2015-2019. Data was solicited from 230 primary school pupils from Grades 3-7, 12 school teachers, two museum directors, two museum curators and seven tour guides. The study reveals that study sheets that are in multiple choice format have been found to promote lower order thinking and guess responses while study sheets that involved drawing, open ended questions, and employing indigenous languages promoted higher order thinking, synthesis and critical thinking. It is concluded that museum study sheets in Zimbabwe mainly promote general and museum-based knowledges as compared to curriculum-based knowledges. This study established pillars needed to be considered when developing effective study sheets that facilitate learning of curriculum content. This study contributes to the promotion of effective heritage education programming in museums.